Hepatitis B core‐related antigen predicts disease progression and hepatocellular carcinoma in hepatitis B e antigen‐negative chronic hepatitis B patients. Issue 10 (16th June 2021) - Kaneko, Shun; Kurosaki, Masayuki; Inada, Kento; Kirino, Sakura; Hayakawa, Yuka; Yamashita, Koji; Osawa, Leona; Sekiguchi, Shuhei; Higuchi, Mayu; Takaura, Kenta; Maeyashiki, Chiaki; Tamaki, Nobuharu; et al.
Abstract: Background and Aim: The serum hepatitis B core‐related antigen (HBcrAg) is considered a surrogate marker of the amount and activity of intrahepatic covalently closed circular DNA. This study aims to investigate the virological characteristics of HBcrAg in chronic hepatitis B (CHB) patients and to reveal the hepatocellular carcinoma (HCC) risk factors of hepatitis B e antigen (HBeAg)‐negative patients. Methods: Hepatitis B core‐related antigen was measured in 245 naive CHB patients before receiving nucleoside/nucleotide analog (NA) therapy. All patients were receiving NA (entecavir, tenofovir disoproxil fumarate, and tenofovir alafenamide) continuously for more than 1 year until the end of follow‐up, and they did not have a history of HCC. Hepatitis B viral status was compared between 106 HBeAg‐positive and 139 HBeAg‐negative patients. Results: Median HBcrAg levels were significantly higher in HBeAg‐positive patients than in HBeAg‐negative patients (> 6.8 vs 3.7 log U/mL, P  < 0.01). In HBeAg‐negative patients, higher HBcrAg levels were associated with cirrhosis (119 chronic hepatitis/20 cirrhosis = 3.5/4.7 log U/mL, P  = 0.03) and higher serum hepatitis B virus DNA. During a median follow‐up of 5.28 (1.03–12.0) years, the 5‐year cumulative HCC incidence rate was 5.4% in the HBeAg‐negative cohort. In the multivariate Cox regression analysis, higher HBcrAg levels at 1 year were independent predictive factors for HCC development in HBeAg‐negative patients who received NA therapy (cutoff value, 4.1 log U/mL; hazard ratio, 6.749; 95% confidence interval, 1.334–34.15, P  < 0.01) and even in non‐cirrhosis patients. Conclusion: Hepatitis B core‐related antigen was useful for understanding disease progression in CHB patients and for stratifying the risk for carcinogenesis in HBeAg‐negative patients receiving NA therapy.